Growth in emergency department self-harm or suicidal ideation presentations in young people: Comparing trends before and since the COVID-19 first wave in New South Wales, Australia. (January 2023) - Sara, Grant; Wu, Jianyun; Uesi, John; Jong, Nancy; Perkes, Iain; Knight, Katherine; O'Leary, Fenton; Trudgett, Carla; Bowden, Michael
Introduction: Self-harm presentations in children and young people have increased internationally over the last decade. The COVID-19 pandemic has the potential to worsen these trends. Objective: To describe trends in emergency department self-harm or suicidal ideation presentations for children and young people in New South Wales before and since the COVID-19 pandemic. Methods: We studied presentations for self-harm or suicidal ideation by 10- to 24-year-olds to New South Wales emergency departments, using interrupted time series analysis to compare annualised growth before COVID (2015 to February 2020) and since COVID (March 2020 to June 2021). Subgroup analyses compared age group, gender, triage category, rurality and disadvantage. Time series decomposition via generalised additive models identified long-term, seasonal and short-term trends. Results: Self-harm or suicidal ideation presentations by young people in New South Wales increased by 8.4% per annum pre-COVID. Growth accelerated since COVID, to 19.2% per annum, primarily due to increased presentations by females aged 13–17 years (47.1% per annum since COVID, from 290 per 10, 000 in 2019 to 466 per 10, 000 in 2021). Presentations in males aged 10–24 years did not increase since COVID (105.4 per 10, 000 in 2019, 109.8 per 10, 000 in 2021) despite growing 9.9% per annum before COVID. Presentation rates accelerated significantly in socio-economically advantaged areas. Presentations in children and adolescents were strongly linked to school semesters. Conclusion: Emergency department self-harm or suicidal ideation presentations by New South Wales young people grew steadily before COVID. Understanding the sustained increase remains a priority. Growth has increased since COVID particularly for adolescent females, but not among adolescent males. Surprisingly, the largest post-COVID increases in annual growth occurred in socio-economically advantaged and urban regions. The COVID-19 pandemic appears to have added new challenges, particularly in females in the developmentally critical early adolescent and teenage years.